Soccer: The 6-week plan. The guide to building a successful team - Schmugge, T. (Meyer & Meyer Sport (UK) Ltd., 2016)
Soccer coaches need to train, practice, and drill players on passing, dribbling, shooting, tactics, and much more. But they often have a hard time finding the best exercises to create a good team. Toto Schmugge, a former professional soccer player from Germany, has created the perfect 6-week plan to help coaches of any skill and experience level give their team a competitive edge and gain confidence as a coach. This plan is especially adjusted to help during pre-season training. These practical training programs were created by professional soccer players and coaches and can be applied to any team. Regardless of the age or talent of the players, with these exercises, they will learn techniques and tactics and improve their strength, speed, endurance, and agility. The exercises are described in detail and very easy to follow. Illustrations for every exercise provide the coach with visual aids to explain the drill. With Toto`s guide, any team will become more successful.